Techno-economic analysis of a 10 kWp utility interactive photovoltaic system at Maungaraki school, Wellington, New Zealand. (1st February 2017) - Emmanuel, Michael; Akinyele, Daniel; Rayudu, Ramesh
Abstract: This paper presents a performance analysis and economic viability of a 10 kWp grid-connected solar photovoltaic (PV) system installed at Maungaraki school, Wellington, New Zealand under the "Dynamis Project". The system consists of 40 panels and two units of 5 kW power converters with a communication capability while the distribution grid serves as a virtual storage. The excess power generated at low load condition during holidays and weekends is exported to the grid. With the system in operation since 2014, performance parameters based on International Energy Agency Photovoltaic Power System Programme (IEA PVPS), Clean Energy Council industry guide and IEC 61724 standard are evaluated. The final yield ranged from 1.1 to 4.9 h/d. The performance ratio (PR) varied between 76 and 79%, giving an annual PR of 78%. In addition, from the economic evaluation of this system at 4%, 6% and 8% discount rates, the levelized cost of energy are 12.1, 14.1 and 16.2 c/kWh respectively, with a simple payback period of 6.4 years. Overall, the total amount of power consumed annually from the grid reduced significantly by 32%. In monetary terms, the school's expenditure on power bills reduced effectively by 45% and was able save about NZD 4700 in 2014. Highlights: Performance analysis and economic viability of a 10 kWp grid-connected PV system are presented. The PR ranged between 76 to 79%, with an annual average value of 78%. The final yield varied between 1.1 to 4.9 h/d, with an annual average value of 2.99 h/d. The LCOE values are 12.1, 14.1 and 16.2 c/kWh at 4%, 6% and 8% discount rates respectively.